Understanding Occupational Gender Segregation Through Students’ Program Choices and Career Interests. - Chaffee, Kathryn Everhart; Plante, Isabelle; Binette-Laporte, Floriane (Sex Roles, 2025)
Although gender gaps in occupational fields have narrowed in many domains, the labor market remains heavily gender segregated. Extending past work focusing primarily on the underrepresentation of women in men-dominated fields, our study examined students’ educational and career interests in both men-dominated and majority-women fields. To do so, the current study examined gender segregation in educational program choices and career interests among 1075 Canadian students (51.9% girls) in their final year of secondary school (age 16), a pivotal turning point before entering either specific postsecondary programs or the workforce. The use of a combination of self-reported and institutional data provided important insights that show how boys and girls differ in the types of fields they plan to study, what jobs they aspire to, and what job characteristics differentiate their interests. Furthermore, person-centered analyses examined how latent profiles of career interest were predicted by stereotypical beliefs. Overall, students of both genders were interested in jobs of equally high salary, but girls were slightly more ambitious than boys in terms of the prestige and required education for their career aspirations. Importantly, the gender segregation of career interests was asymmetrical, with boys being more interested in gender-typical careers than girls. This study provided a nuanced portrait of the role of job characteristics and gender-stereotypical beliefs in occupational gender segregation, which is important for understanding the barriers and facilitators to gender equity in job aspirations across occupational fields.